The look of lyric : Greek song and the visual studies in archaic and classical Greek song - Cazzato, Vanessa, 1977-; Lardinois, A. P. M. H. (Mnemosyne, Supplements, 2016)
The Look of Lyric: Greek Song and the Visual addresses the various modes of interaction between ancient Greek lyric poetry and the visual arts as well as more general notions of visuality. It covers diverse poetic genres in a range of contexts radiating outwards from the original performance(s) to encompass their broader cultural settings, the later reception of the poems, and finally also their understanding in modern scholarship. By focusing on the relationship between the visual and the verbal as well as the sensory and the mental, this volume raises a wide range of questions concerning human perception and cultural practices. As this collection of essays shows, Greek lyric poetry played a decisive role in the shaping of both.